Papers - Production - Foreign - Petroleum in Bahrein Island in 1940 (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1941)
During 1940, the Bahrein Island field produced a total of 7,073,919 bbl. of crude oil- an average of 19,328 bbl. per day. This is a decline of 514,635 bbl. from the I939 production of 7,588,554 bbl. At the end of 1940, there were 70 producing wells.